PELAYANAN PENEMPATAN TENAGA KERJA PADA DINAS TENAGA KERJA KOTA PEKANBARU - Erni Wiharti; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Employment placement service in human resources office Pekanbaru city. Thisstudy aims to determine the implementation of employment service in human resourcesoffice in the city seweto and the factors that influence it. This study uses the theory of LPsinambela using qualitative research methods with techniques of data collection andinterviews, observation and documentation through research informants who have beenassigned based on snowball sampling technique.Keywords: services, placement,man power